Impact of Geothermal Wastewater Drainage on Arsenic Species in Environmental Media: A Case Study at the Yangbajing Geothermal Field, Tibet, China - Guo, Qinghai; Wang, Yanxin (Procedia earth and planetary science, 2013)
The high temperature geothermal fluids from the Yangbajing geothermal field, Tibet, have been used for electricity generation. The geothermal wastewater generated by the Yangbajing power plants, with arsenic (As) concentrations up to 3.18mg/L, was drained immediately into the Zangbo River, which markedly increased the arsenic concentration of river water downstream from the wastewater discharges. However, along the flow direction of the river, arsenic concentrations in water declined sharply. Further inspection shows that the concentrations of weakly- bound As, strongly-adsorbed As, and total As in riverbed sediment were also affected by the drainage of geothermal wastewater, indicating that the sediment may serve as a sink for arsenic from the geothermal source. After arsenic from geothermal wastewater entered the Zangbo River, the adsorption of arsenic on riverbed sediment lowers the arsenic concentrations in the river water, reducing the health threat of arsenic to local residents using the river as a drinking water source.